Pengaruh Independensi, Profesionalisme, Skeptisme Profesional, Etika Profesi dan Gender Terhadap Kualitas Audit Pada KAP di Bali - Rahayu, Ni Kadek Sri; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 30 No 3 (2020)DO - 10.24843/EJA.2020.v30.i03.p11, 2020)
This study aims to determine the effect of professionalism and gender professionalism independence on audit quality at public accounting firms in Bali. Data collection methods in this study used a questionnaire. The population in this study are all auditors who work at the Public Accounting Firm in Bali with a total of 78 auditors overall. The analysis technique used is Multiple Linear Regression. Based on the analysis and testing of hypotheses, the conclusion is that (1) independence has a positive effect on audit quality, (2) professionalism has a positive effect on audit quality, (3) professional skepticism has a positive effect on audit quality, (4) professional ethics has a positive effect on quality audit (5) gender negatively influences audit quality. Keywords : Independence; Professionalism; Ethics; Gender; Audit Quality.